THE INFLUENCE OF CUPPING THERAPY ON BLOOD PRESSURE REDUCTION IN HYPERTENSIVE PATIENTS AT THE HOLISTIC HEALTH HOUSE OF FIYAS IN CENDANA VILLAGE, BANGGAI REGENCY - Nur Ayun R. Yusuf; Ilyas M. Ali (PROFESSIONAL HEALTH JOURNAL, 2025)
Intriduction: Hypertension is defined as an increase in systolic blood pressure of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg measured twice with a five-minute interval in a state of sufficient rest or relaxation (Ministry of Health of the Republic of Indonesia, 2018). Systolic blood pressure > 130 mmHg and diastolic blood pressure > 80 mmHg in adults (Asmah, 2023). Persistent and uncontrolled hypertension is a leading cause of death, leading to myocardial infarction, heart failure, kidney failure, stroke, vision disorders, and peripheral vascular disease Objectives: The purpose of this study is to examine the effect of cupping therapy on blood pressure reduction in hypertensive patients Method: The design used in this study is Quasi-Experimental, involving a control group and an intervention group. Results: Based on the research results, the average systolic blood pressure at the final measurement for the intervention group is 140.76, while the average systolic blood pressure for the control group is 150.29, with a total of 34 participants. The statistical test using the Paired Sample T-test yielded a value of P 0.002, which is less than 0.05. Therefore, it can be concluded that there is an effect of cupping therapy on blood pressure reduction in hypertensive patients. Meanwhile, the average diastolic blood pressure at the final measurement for the intervention group is 84.24, while the average diastolic blood pressure for the control group is 94.71, also with a total of 34 participants. The statistical test using the Paired Sample T-test yielded a value of P 0.000, which indicates P < 0.05. Conclusions: based on results can be concluded that there is an effect of cupping therapy on blood pressure reduction in hypertensive patients